Experiments in international adjudication : historical accounts / edited by Ignacio de la Rasilla, Jorge E. Viñuales. - Rasilla, Ignacio de la; Viñuales, Jorge E. (Cambridge University Press, 2019)
The history of international adjudication is all too often presented as a triumphalist narrative of normative and institutional progress that casts aside its uncomfortable memories, its darker legacies and its historical failures. In this narrative, the bulk of 'trials' and 'errors' is left in the dark, confined to oblivion or left for erudition to recall as a curiosity. Written by an interdisciplinary group of lawyers, historians and social scientists, this volume relies on the rich and largely unexplored archive of institutional and legal experimentation since the late nineteenth century to shed new light on the history of international adjudication. It combines contextual accounts of failed, or aborted, as well as of 'successful' experiments to clarify our understanding of the past and present of international adjudication.